Neuronal hypertrophy dampens neuronal intrinsic excitability and stress responsiveness during chronic stress. (24th May 2020) - Matovic, Sara; Ichiyama, Aoi; Igarashi, Hiroyuki; Salter, Eric W.; Sunstrum, Julia K.; Wang, Xue Fan; Henry, Mathilde; Kuebler, Eric S.; Vernoux, Nathalie; Martinez‐Trujillo, Julio; Tremblay, Marie‐Eve; Inoue, Wataru
Abstract : Key points: The hypothalamic‐pituitary‐adrenal (HPA) axis habituates to repeated stress exposure. We studied hypothalamic corticotropin‐releasing hormone (CRH) neurons that form the apex of the HPA axis in a mouse model of stress habituation using repeated restraint. The intrinsic excitability of CRH neurons decreased after repeated stress in a time course that coincided with the development of HPA axis habituation. This intrinsic excitability plasticity co‐developed with an expansion of surface membrane area, which increased a passive electric load and dampened membrane depolarization in response to the influx of positive charge. We report a novel structure–function relationship for intrinsic excitability plasticity as a neural correlate for HPA axis habituation. Abstract: Encountering a stressor immediately activates the hypothalamic‐pituitary‐adrenal (HPA) axis, but this stereotypic stress response also undergoes experience‐dependent adaptation. Despite the biological and clinical importance, how the brain adjusts stress responsiveness in the long term remains poorly understood. We studied hypothalamic corticotropin‐releasing hormone neurons that form the apex of the HPA axis in a mouse model of stress habituation using repeated restraint. Using patch‐clamp electrophysiology in acute slices, we found that the intrinsic excitability of these neurons substantially decreased after daily repeated stress in a time course that coincided with their loss of stress responsiveness in vivo . This intrinsic excitability plasticity co‐developed with an expansion of surface membrane area, which increased a passive electric load, and dampened membrane depolarization in response to the influx of positive charge. Multiphoton imaging and electron microscopy revealed that repeated stress augmented ruffling of the plasma membrane, suggesting an ultrastructural plasticity that may efficiently accommodate the membrane area expansion. Overall, we report a novel structure–function relationship for intrinsic excitability plasticity as a neural correlate for adaptation of the neuroendocrine stress response. Key points: The hypothalamic‐pituitary‐adrenal (HPA) axis habituates to repeated stress exposure. We studied hypothalamic corticotropin‐releasing hormone (CRH) neurons that form the apex of the HPA axis in a mouse model of stress habituation using repeated restraint. The intrinsic excitability of CRH neurons decreased after repeated stress in a time course that coincided with the development of HPA axis habituation. This intrinsic excitability plasticity co‐developed with an expansion of surface membrane area, which increased a passive electric load and dampened membrane depolarization in response to the influx of positive charge. We report a novel structure–function relationship for intrinsic excitability plasticity as a neural correlate for HPA axis habituation.